Low-temperature thermochronology and its geological significance in the central-northern section of the western margin of the Ordos Basin - G. Xing; G. Xing; Z. Ren; Z. Ren; K. Qi; K. Qi; S. Guo; S. Guo; Y. Liu; Y. Liu; Y. Zhang; H. Lan (Solid Earth)
The study of low-temperature thermochronology at plate edges provides favourable constraints for regional tectonic evolution and surface processes. Based on the existing thermochronological data of multiple cooling events since the Mesozoic era, we conducted apatite fission-track and (U–Th) /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1b4178c77ca0d4bfee6c9ddd864f3a43"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="se-16-709-2025-ie00001.svg" width="8pt" height="14pt" src="se-16-709-2025-ie00001.png"/></svg:svg> He dating studies on drilling samples from the central-northern section of the western margin of the Ordos Basin, revealing the exhumation and cooling history, including differences, in the study area. The new thermal-history inverse modelling results show that the Zhuozishan Mountain region (ZM region) experienced large-scale exhumation in the Late Jurassic (160–150 Ma), with an average exhumation rate of ca. 45 m Ma−1 and an average cooling rate of ca. 2 °C Ma−1; slow exhumation in the Early Cretaceous–Oligocene (130–30 Ma), with an average exhumation rate of ca. 10 m Ma−1 and an average cooling rate of ca. 1 °C Ma−1; and severe exhumation after the Oligocene (30 Ma–present), with an average exhumation rate of ca. 30 m Ma−1 and an average cooling rate of ca. 1.2 °C Ma−1. The Taole–Hengshanbao region (TH region) started exhumation in the Late Jurassic–Early Cretaceous (155–145 Ma), with an average exhumation rate of ca. 48 m Ma−1 and an average cooling rate of ca. 2.4 °C Ma−1; underwent slow exhumation in the Early Cretaceous–Oligocene (145–30 Ma), with an average exhumation rate of ca. 7.5 m Ma−1 and an average cooling rate of ca. 0.3 °C Ma−1; and then underwent violently exhumation, with an average exhumation rate of ca. 25 m Ma−1 and an average cooling rate of ca. 1 °C Ma−1. The Majiatan–Huianbao region (MH region) experienced large-scale exhumation in the Late Jurassic–Early Cretaceous (158–137 Ma), with an average exhumation rate of ca. 45 m Ma−1 and an average cooling rate of ca. 1.8 °C Ma−1; featured a slightly slower exhumation rate at 137–110 Ma, with an average exhumation rate of ca. 13 m Ma−1 and an average cooling rate of ca. 0.52 °C Ma−1; and entered a severe exhumation stage again in the Late Cretaceous–Eocene (70–50 Ma), with an average exhumation rate of ca. 37.5 m Ma−1 and an average cooling rate of ca. 1.5 °C Ma−1. The Late Jurassic tectonic exhumation indicated by thermochronology corresponds to the formation of the western-margin fold-and-thrust belt, with the northern and southern sections starting earlier and the central section starting slightly later. At the same time, the exhumation time of different fault blocks decreased gradually from the edge of the basin towards the centre, following an E–W direction. This is related to the different tectonic evolution and stress patterns in the different locations.